2005
DOI: 10.4049/jimmunol.175.4.2056
|View full text |Cite
|
Sign up to set email alerts
|

Cutting Edge: Chemoattractant Receptor-Homologous Molecule Expressed on TH2 Cells Plays a Restricting Role on IL-5 Production and Eosinophil Recruitment

Abstract: PGs play key regulatory roles in inflammation and immunity. PGD2, released from mast cells and Th2 cells during allergic responses, has recently been shown to target a novel receptor, chemoattractant receptor-homologous molecule expressed TH2 cells (CRTH2), in addition to the classic PGD (DP) receptor. CRTH2 is expressed on Th2 cells and eosinophils and mediates chemotaxis of these cells to PGD2. Thus, CRTH2 is thought to be a key receptor mediating eosinophil and Th2 cell recruitment during allergic responses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
63
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(66 citation statements)
references
References 23 publications
3
63
0
Order By: Relevance
“…The role of the CRTH2 receptor on the pathogenesis of allergic inflammation remains controversial. Although CRTH2 receptor antagonists have been found effective to suppress inflammation (48), CRTH2-deficient mice developed more severe inflammation of the airways compared with wild-type mice (49). However, in our model of virus infection-induced airway and airspace inflammation, pharmacological blockade or genetic deletion of CRTH2 each successfully suppressed airway inflammation.…”
Section: Discussionmentioning
confidence: 64%
“…The role of the CRTH2 receptor on the pathogenesis of allergic inflammation remains controversial. Although CRTH2 receptor antagonists have been found effective to suppress inflammation (48), CRTH2-deficient mice developed more severe inflammation of the airways compared with wild-type mice (49). However, in our model of virus infection-induced airway and airspace inflammation, pharmacological blockade or genetic deletion of CRTH2 each successfully suppressed airway inflammation.…”
Section: Discussionmentioning
confidence: 64%
“…Through activation of CRTH2, PGD 2 promotes the migration of eosinophils, basophils, and Th2 cells (6,9,10) and has the unusual ability to stimulate Th2 cytokine production (11) even in the absence of allergen recognition or costimulation (12). Initial studies with CRTH2 knockout mice (13) suggested that CRTH2 might constrain Th2 cytokine production and promote Th1 cytokine production, but this is likely to be due to CRTH2 expression by Th1 cells in mice and the particular immunization procedures used. More recent studies with selective CRTH2 antagonists and genetically deficient mice have highlighted an important role for CRTH2 in promoting the accumulation of lymphocytes and eosinophils (14,15) and the production of Th2 cytokines (16) and IgE (14,16) at sites of allergic inflammation.…”
Section: Novel Function Of Crth2 In Preventing Apoptosis Of Human Th2mentioning
confidence: 99%
“…For example, PGD 2 was shown to reinforce airway inflammation via the DP receptor in a murine asthma model 11 , whereas a selective CRTH2 agonist was shown to exacerbate allergic asthma and atopic dermatitis 12 . In contrast to these reports, the administration of a DP agonist reduced T-cell activation and alleviated symptoms of atopic dermatitis 24 , and CRTH2 agonism restricted eosinophil infiltration in allergic airway inflammation 13 . These observations were obtained by exogenous administration of PGD 2 -associated agents both in vitro and in vivo.…”
Section: Discussionmentioning
confidence: 49%
“…In mouse asthma model, DP agonism reduced eosinophilia and airway hyperresponsiveness 12 , whereas CRTH2 agonism restricted the recruitment of eosinophils by limiting the production of interleukin (IL)-5 (ref. 13). Thus, the role of PGD 2 signalling in allergic response remains poorly understood.…”
mentioning
confidence: 99%